Observation of four-electron Auger processes. (November 2015) - Müller, A; Borovik, A; Buhr, T; Hellhund, J; Holste, K; Kilcoyne, A L D; Klumpp, S; Martins, M; Ricz, S; Viefhaus, J; Schippers, S
Abstract: Multiple ionization of ions subsequent to absorption of a single photon has been studied employing a photon-ion merged-beam setup at the PETRA III synchrotron radiation facility of DESY in Hamburg. Absolute cross sections for single, double and triple ionization of C + ions were measured with emphasis on specific well defined terms of K-shell excited C + . In particular, the terms C + (1 s 2 s 2 2 p 2 2 D, 2 P) were excited from the ground level of C + . Subsequent autoionization processes resulted in the production of C 2+, C 3+ and C 4+ ions. The associated decay mechanisms are single-Auger, double-Auger and triple-Auger decay. The observation of C 4+ products arising from C + (1 s 2 s 2 2 p 2 2 D, 2 P) unambiguously confirmed the existence of triple-Auger decay, i.e., a process in which 4 electrons interact with one another such that one fills the K-shell vacancy and the others are simultaneously ejected. The experiment yields branching ratios for the Auger decay channels as well as individual decay rates for autoionization and radiative stabilization of the C + (1 s 2 s 2 2p 2 2 D, 2 P) terms.